Pendampingan Pembuatan Lembar Kerja Peserta Didik (LKPD) dengan Metode Proyek pada Guru-Guru SDN No 106193 Bakaran Batu - Hasanah Hasanah; Nurdiana Siregar (Journal of Social Responsibility Projects by Higher Education Forum, 2022)
This community partnership program (PKM) service activity is carried out with the aim of (1) providing knowledge and understanding to teachers regarding student worksheets (LKPD) with the project method starting from the planning, implementation and project-based assessment stages, (2) guiding teachers by providing assistance in making student worksheets (LKPD) using the project method, (3) training teacher creativity in developing learning tools. The PKM service partners are teachers at SDN No 106193 Bakaran Batu Kec. Mirror beach. The method used in this activity is training, discussion, mentoring. This activity was held in September 2022. Training and discussions were held for 2 days at SDN No 106193 Bakaran Batu followed by 1 month of mentoring. The outputs achieved from the results of community service activities that have been carried out at SDN No 106193 Bakaran Batu Kec. Pantaimirmiri is that teachers understand about making student worksheets (LKPD) with the project method, teachers succeed in making student worksheets (LKPD) with the project method, teachers can design learning tools well, especially making LKPD with the project method and apply it in learning.